OVERVIEW OF THE EPIZOOTIC SITUATION ON RABIES FOR 2015 IN THE RUSSIAN FEDERATION - SHABEYKIN A.A.; GULYUKIN A.M. (Редакция журнала Russian Journal of Agricultural and Socio-Economic Sciences, 2016)
The area of rabies in the Russian Federation in recent years covered a large part of the regions of the country. The number of affected animals and the location of disadvantaged areas are permanently and significantly changing, but all of these variations in most cases occur for natural reasons, the study of which allows to understand better the mechanisms of development of the epidemic. The number annual of rabies outbreaks in our country is higher compare with other anthropozoonotic diseases. Rabies in Russian Federation was registered at stably high levels during 2015, with the epizootic process being more intensive at the administrative districts of Central, Privolzhski, and Southern Federal regions. The major rabies reservoir in Russia are wild canines, mostly foxes, raccoon dogs, arctic foxes, wolfs, jackals, corsac foxes. Creation a zonal immune protection around residential areas should be part of an oral vaccination program for wild carnivores in order to minimize the epidemiologic risks.